Establishment Of In Vitro Culture Techniques For Clinacanthus Nutans And The Evaluation On Its Antioxidant Potential - Bong, Fui Joo (2021)
Clinacanthus nutans (Burm.f.) Lindau is a valuable traditional medicinal plant that has gained interest as an alternative side treatment for cancer, particularly in South East Asia. Phenolic and flavonoid compounds identified in this plant have been linked to its anti-cancer properties due to their antioxidant activity in scavenging radical species. The present study aims to establish callus and cell suspension cultures of C. nutans and to evaluate the accumulation of phenolics, flavonoids and antioxidant activity from extracts of in vitro cultures (callus and cell suspension cultures) and intact plants parts (leaf and stem). Different plant growth regulators (2, 4-D and BAP, picloram) and combinations of auxin (2, 4-D or NAA) and cytokinin (BAP, TDZ or KIN) were used for the induction of friable callus. Besides, different proliferation medium and sucrose concentrations were tested on callus proliferation. Growth kinetics of two suspension cell lines was studied. The total phenolic and total flavonoid contents as well as the antioxidant activity of the extracts from intact plants and in vitro cultures were evaluated using spectrophotometric analysis. High-performance liquid chromatography (HPLC) analysis was performed to detect the selected flavonoids. Friable and pale-yellow callus was induced from young leaf explants of C. nutans on MS medium augmented with 2, 4-D and BAP whereas compact and brownish callus was induced on medium supplemented with picloram. Friable callus with maximum biomass (0.623 ± 0.016 g) was produced on MS medium supplemented with a combination of 0.25 mg/L 2, 4-D and 0.25 mg/L BAP.